Assessment of a Smartphone-Based Neural Network Application for the Risk Assessment of Skin Lesions under Real-World Conditions - Teresa Maria Kränke; Philipp Efferl; Katharina Tripolt-Droschl; Rainer Hofmann-Wellenhof (Dermatology Practical & Conceptual)
Introduction: The diagnostic performance of convolutional neural networks (CNNs) in diagnosing different types of skin cancer has been quite promising. Mobile phone applications with integrated artificial intelligence (AI) are an understudied area.